DEVELOPMENT OF AN ACTIVE LEARNING MODEL BASED ON THE K-SLAVE CONCEPT TO ENHANCE INNOVATIVE CREATIVE THINKING FOR LEARNING MANAGEMENT OF GRADUATE STUDENT TEACHERS - Dechpanprasong, Warisanan (Journal of MCU Nakhondhat, 2026)
This research aimed to: 1) Develop an active learning management model based on the K-SLAVE concept for graduate student teachers; 2) Examine the effects of implementing the model based on the K-SLAVE concept for graduate student teachers; and 3) Evaluate graduate student teachers’ satisfaction with the K-SLAVE–based active learning model. The study employed a research-and-development design with a mixed-methods approach, conducted in two phases. Phase 1 involved developing the K-SLAVE active learning model through a review and analysis of relevant theories and literature, drafting the model comprising five components, and validating its quality through expert review by five specialists. Phase II consisted of implementing the model with 25 graduate student teachers. The research instruments included: 1) 5 Active learning lesson plans, 2) A learning innovation creative skills assessment form, and 3) A graduate student teachers’ satisfaction assessment form regarding the K-SLAVE active learning model. Data were analyzed using descriptive statistics, inferential statistics (t-test), and qualitative content analysis. The findings revealed that: 1) The developed learning management model comprised five components: rationale and significance, principles, objectives, learning procedures, and measurement and evaluation. The model was rated at the highest level of appropriateness by the experts. and 2) The participants’ innovative learning design skills, both overall and by dimension, showed significantly higher post-test scores than pre-test scores. The results were consistent with peer and instructor evaluations, which also indicated that the participants demonstrated innovative learning design skills at the highest level. Furthermore, the participants’ satisfaction with the K-SLAVE–based active learning model was at the highest level.